2016
DOI: 10.1515/ii-2017-0123
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Relationship Between Oral Microbial Community and Tumor

Abstract: Significant progress was observed in studies of the relationship between oral Helicobacter pylori and gastric cancer and tumors. Based on three distinct and close relationships, namely, the relationship between oral H. pylori and gastric cancer, between oral microbial communities and oral squamous cell carcinoma, and between oral microbial communities of human immunodeficiency virus-infected patients and tumors, this work reviews the relationship between oral microbial communities and tumors. This research als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Chemokines can promote cell migration and invasion by inducing the proliferation of cancer cells and preventing their apoptosis. [13][14][15][16] Although compelling evidence showed that carcinogenesis can be modulated by microbiota, specifically an association between microbiota in the oral cavity with oral cancer, its composition and diversity in oral cancer patients remain unclear. A big question remains: what are the oral microbiota composition and diversity found in oral cancer patients that may influence an individual's oral cancer risk?…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines can promote cell migration and invasion by inducing the proliferation of cancer cells and preventing their apoptosis. [13][14][15][16] Although compelling evidence showed that carcinogenesis can be modulated by microbiota, specifically an association between microbiota in the oral cavity with oral cancer, its composition and diversity in oral cancer patients remain unclear. A big question remains: what are the oral microbiota composition and diversity found in oral cancer patients that may influence an individual's oral cancer risk?…”
Section: Introductionmentioning
confidence: 99%